Early yaws, imported in The Netherlands. - Engelkens, H J (1989)
Early yaws in a 9 year old girl from Ghana, diagnosed as imported disease in The Netherlands is reported. She had lived in The Netherlands for six months. Tropical non-venereal treponematoses are rarely seen in Europe, and only a few case reports have been published. Migration and travelling may confront the medical profession with cases of tropical diseases such as yaws. Positive serological reactions in non-venereal tropical or venereal treponematoses cannot be distinguished at present.